2017
DOI: 10.1021/acs.jpcc.7b10295
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Effect in Vis–NIR Emission of Sm3+-Doped GeO2–PbO Glasses

Abstract: Spectroscopic and structural properties of GeO 2 −PbO glasses doped with Sm 3+ ion were investigated before and after densification at 7.7 GPa using Xray difraction, Raman spectroscopy, ellypsometry, Extended X-ray absorption fine structure (EXAFS) and absorption and luminescence spectroscopy. Judd−Ofelt (J− O) intensity parameters Ω λ (λ = 2, 4, and 6) were calculated and the Ω 2 parameter decreased for the glass after densification at 7.7 GPa due to the structural changes of the host glass induced by pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…After densification at 7.7 GPa, these bands shifted to lower energies, indicating an irreversible pressure-induced modification in the glass network. This result is consistent with a previous investigation of the effect of densification under high pressure of the same glass host doped with Sm 3+ , based on experimental results obtained from Raman spectroscopy and extended X-ray absorption fine structure techniques . It that case, high pressure induced a decrease in the number of GeO 4 tetrahedral units and an increase in the GeO 6 octahedral units.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…After densification at 7.7 GPa, these bands shifted to lower energies, indicating an irreversible pressure-induced modification in the glass network. This result is consistent with a previous investigation of the effect of densification under high pressure of the same glass host doped with Sm 3+ , based on experimental results obtained from Raman spectroscopy and extended X-ray absorption fine structure techniques . It that case, high pressure induced a decrease in the number of GeO 4 tetrahedral units and an increase in the GeO 6 octahedral units.…”
Section: Resultssupporting
confidence: 93%
“…This result is consistent with a previous investigation of the effect of densification under high pressure of the same glass host doped with Sm 3+ , based on experimental results obtained from Raman spectroscopy and extended X-ray absorption fine structure techniques. 30 It that case, high pressure induced a decrease in the number of GeO 4 tetrahedral units and an increase in the GeO 6 octahedral units. Since the octahedral configuration presents a higher packing density than the tetrahedral configuration, this effect should be expected after densification of the glass host.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The predicted bulk modulus was 40–50 GPa, depending on the final amorphization state. These results agree with experimental parameters calculated from the analysis of extended X-ray absorption fine structure (EXAFS) . In conclusion, MD indicates that the local environment around the Er +3 ion is probably strongly coupled to Ge–O tetrahedral substructures, which have a phonon energy around 792 cm –1 , according to the Raman spectra of the glassy 59GeO 2 -41PbO system …”
Section: Resultssupporting
confidence: 86%
“…The structural properties of GeO 2 –PbO glass have been largely addressed by experimental techniques. For 59GeO 2 -41PbO glass composition, differential thermal analysis (DTA) and X-ray diffraction (XRD) experimental results indicated that the local arrangement that prevails is PbGeO 3 …”
Section: Computational Simulationmentioning
confidence: 99%